REVEALING RELATIONSHIP CAPITALISM, DEMOCRACY AND GLOBALIZATION IN CRITICAL LEGAL STUDIES APPROACH - FX.Adji Samekto (Fakultas Hukum, Universitas Diponegoro, 2017)
The dominance of global capitalism is the result of a long historical process in Western Europe since the Enlightenment in the seventeenth century, the philosophers led by a very large influence on the political-economic thought and legal relationship with the state and its citizens.Capitalism and free market mechanisms become increasingly strong with sustained legal concept of rule of law. The principle of the rule of law actually originally not intended to be a means of achieving public objectives or to solve the problems of society such as the problem of poverty. Rule of law is intended to create a stable structure for individuals and businesses associated with economic activities.Linkage between laissez faire, the rule of law is logically implicated in the growth of the view that the existence of the state is to protect the free market. That is phenomena of globalization. The dominance of the rules of law which is intended to facilitate the interests of the free market encourage the implementation of adjustment programs by the state in Third World. As a result, however, it become difficult to realize policies in favor of poverty, meeting basic needs and alignments on the rights of local communities, the embodiment of social justice and environmental protection.